2021
DOI: 10.1016/j.celrep.2021.109784
|View full text |Cite
|
Sign up to set email alerts
|

Potent neutralization of SARS-CoV-2 variants of concern by an antibody with an uncommon genetic signature and structural mode of spike recognition

Abstract: The emergence of SARS-CoV-2 lineages that are more transmissible and resistant to currently approved antibody therapies poses a considerable challenge to the clinical treatment of COVID-19. Therefore, the need for ongoing discovery efforts to identify broadly reactive monoclonal antibodies to SARS-CoV-2 is of utmost importance. Here, we report a panel of SARS-CoV-2 antibodies isolated using the LIBRA-seq technology from an individual who recovered from COVID-19. Of these antibodies, 54042-4 shows potent neutra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 71 publications
1
20
0
Order By: Relevance
“…54042-4 uses a distinct S protein recognition mode and possesses a distinctive genetic signature, differentiating it from other SARS-CoV-2 neutralizing antibodies. Its ability to neutralize Alpha, Beta, Gamma, and Delta VOCs and conservancy of its epitope among currently circulating isolates make it a potential therapeutic and diagnostic target ( Kramer et al, 2021 ).…”
Section: Therapeutic Advances Against Omicronmentioning
confidence: 99%
“…54042-4 uses a distinct S protein recognition mode and possesses a distinctive genetic signature, differentiating it from other SARS-CoV-2 neutralizing antibodies. Its ability to neutralize Alpha, Beta, Gamma, and Delta VOCs and conservancy of its epitope among currently circulating isolates make it a potential therapeutic and diagnostic target ( Kramer et al, 2021 ).…”
Section: Therapeutic Advances Against Omicronmentioning
confidence: 99%
“…Using sera from individuals infected during wave 1 in the United Kingdom (UK), it was found that while the cross-neutralization of different SARS-CoV-2 VOC lineages is reduced, the sera neutralize the VOCs and parental virus to similar levels [24]. Another study found that a naturally infected individual produced uncommon genetic and structural characteristics and showed potent neutralization against authentic SARS-CoV-2 viruses, including VOCs [32]. These results are consistent with other reports [33][34][35] and highlight the need for more epidemiological data about the contribution of previously exposed individuals with naturally-acquired immunity to herd immunity.…”
Section: Discussionmentioning
confidence: 99%
“…It promotes a significant change in free energy (− 1.92 kcal/mol), contributing to a higher binding to the receptor, using Alpha and Beta variants as a model [ 204 ]. Helped, along with N460K and E484K, to strengthen de electrostatic complementarity between RBD and ACE2 [ 206 , 212 , 213 ]. In contrast, another study found low effects on biding by this mutation alone [ 211 ].…”
Section: The Spike Protein (S) Of Sars-cov-2: Clinical Interest and N...mentioning
confidence: 99%
“…Also, despite arginine being a non-aromatic amino acid, it is involved with π-stacking interactions and conformation flexibility; therefore, the author suggested that this could be the reason why this combination is more tolerated [ 208 ] a N501Y b RBD Beta and Gamma - Clinical: it seems to increase infectivity, improving binding free energy by 0.55 kcal/mol [ 179 , 190 ] - Immune: evidence of immune evasion to mAbs [ 184 , 190 ] - Structural: increases RBD stability and High ACE2 binding affinity by 10-folds [ 120 , 160 , 186 , 190 , 214 ]. Paired up with Q498R mutation enhances affinity for ACE-2 dramatically, about fourfold above N501Y alone [ 137 , 206 ]. Also part of an “interface-destabilizing” group and independently can strongly impact hACE2 biding [ 187 ] Y505H RBD - Immune: together with E484A and Y505H, increased the evasion power of Omicron, compared with Delta variant, against 132 antibodies [ 179 ].…”
Section: The Spike Protein (S) Of Sars-cov-2: Clinical Interest and N...mentioning
confidence: 99%
See 1 more Smart Citation